2022
DOI: 10.1002/hsr2.764
|View full text |Cite
|
Sign up to set email alerts
|

Impaired wound healing is associated with poorer mood and reduced perceived immune fitness during the COVID‐19 pandemic: A retrospective survey

Abstract: Background and Aims The coronavirus disease‐2019 (COVID‐19) pandemic disrupted medical care of patients with chronic wounds, and in combination with other negative effects of lockdown measures, this may have a negative effect on mood and quality of life. Until now, the consequences of the COVID‐19 pandemic and associated lockdowns for individuals with impaired wound healing have not been investigated. Methods An online survey was conducted to evaluate perceived immune f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Acute systemic and topical viral infections including COVID-19 and herpes are usually associated with cell injuries and wounds that persist for longer times after termination of viral replication and shedding [ 34 ]. In addition, the COVID-19 pandemic is meaningfully associated with many social factors including depression that affect immune fitness [ 21 ], delaying the wound healing process [ 3 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute systemic and topical viral infections including COVID-19 and herpes are usually associated with cell injuries and wounds that persist for longer times after termination of viral replication and shedding [ 34 ]. In addition, the COVID-19 pandemic is meaningfully associated with many social factors including depression that affect immune fitness [ 21 ], delaying the wound healing process [ 3 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 restrictions also limited the care of wound patients [10,11]. Outpatient wound clinics across Germany were closed for several weeks at the beginning of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted before the pandemic among the same age group in The Netherlands revealed that, compared to healthy controls, young adults with self-reported impaired wound healing reported poorer mood [17], poorer sleep [18], lower quality of life [17], impaired attention and increased impulsivity [19], and a poorer immune fitness [20]. One study revealed that during the pandemic, significant lockdown effects were evident for both healthy controls and the group with self-reported impaired wound healing [11]. However, the negative effects on mood and immune fitness were significantly more pronounced among the impaired wound-healing group.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis of 634,338 COVID-19 patients revealed that having mental disorders was also associated with an unfavorable disease course once infected with SARS-CoV-2, including greater symptom severity and increased mortality rates [31]. A recent study demonstrated this difference by comparing individuals with and without self-reported impaired wound healing (e.g., slow-healing wounds and infections) (See Figure 4) [32]. Previous studies showed that impaired wound healing was associated with a poorer mood and quality of life [33], poorer immune fitness and experiencing more immune-related complaints [34], and various negative health consequences, such as poorer sleep quality [35] and experiencing more gastrointestinal complaints [36].…”
mentioning
confidence: 99%
“…For each time period, significant (p < 0.0167) differences between individuals with impaired wound healing (striped bars) and individuals without impaired wound healing (white bars) are indicated with *. Data from references [10,32]. Permission to use the background image was obtained from Depositphotos.…”
mentioning
confidence: 99%